2016
DOI: 10.5588/ijtld.15.0733
|View full text |Cite
|
Sign up to set email alerts
|

Modified cytospin slide microscopy method for rapid diagnosis of smear-negative pulmonary tuberculosis

Abstract: The sensitivity of our modified method was significantly higher than that of direct or concentrated smears. Overall, the modified method improved the detection rate of AFB in BALF specimens, and provided an efficient and accurate diagnosis of PTB in patients with suspected smear-negative PTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…The sensitivity of concentrated method in our study was 36.5%. Similar results have been reported by other studies 11,19 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The sensitivity of concentrated method in our study was 36.5%. Similar results have been reported by other studies 11,19 .…”
Section: Discussionsupporting
confidence: 93%
“…We used the BAL samples directly without any prior treatment since there was no clogging during our pilot study. Also we used the cytospin settings of 1000g for 5 minutes, different from that used by Zheng et al who used 250 for 5 minutes 11 . During the pilot study we compared both settings and found no difference in results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La positividad global de nuestros resultados se diferencia notablemente de los de un estudio en Pakistán, donde se obtuvo una positividad de 49,7 % con la PCR, de 47,8 % con el cultivo y de 40 % con la coloración de Ziehl-Neelsen a partir de muestras pulmonares; en dicho estudio, la PCR obtuvo una mayor positividad que el cultivo, por lo que se la consideraría como la prueba de referencia (14). Específicamente en el lavado broncoalveolar, un estudio en el que se utilizó el procesamiento en un equipo Cytospin™ y una modificación del método de coloración de Ziehl-Neelsen, la sensibilidad de la coloración estuvo entre 16,2 y 37,8 %, muy por debajo de la sensibilidad obtenida en nuestro estudio (15). La variabilidad en los resultados de las pruebas, especialmente en cuanto a la positividad global y la sensibilidad, se puede deber a múltiples factores: algunos previos al análisis relacionados con la conservación y el transporte de las muestras que pueden afectar los resultados de las técnicas de detección, así como la preparación y conservación de los reactivos para la coloración de Ziehl-Neelsen y la concentración de las soluciones, así como factores analíticos como la experiencia profesional del personal que interpreta los extendidos (16).…”
Section: Discussionunclassified